THE RELATIONSHIP BETWEEN FAMILY RESILIENCE AND REPRODUCTIVE HEALTH BEHAVIOUR WITH ATTITUDES TOWARDS EARLY MARRIAGE IN ADOLESCENTS IN STATE JUNIOR HIGH SCHOOL X PARUNG PANJANG - ritanti, Ritanti; Pertiwi, Nurhanifasyah (Jurnal Keperawatan, 2025)
Adolescents are the future successors of the nation who are vulnerable to deviant reproductive health behaviour, which will have an impact such as early marriage. This study aims to determine the relationship between family resilience and reproductive health behaviour with attitudes towards early marriage in adolescents at State Junior High School X Parung Panjang. This research design uses quantitative observational analytic cross-sections approach with stratified random sampling technique. A total of 285 students of State Junior High School X Parung Panjang participated in the study. Univariate data analysis using proposi test and bivariate analysis using Chi-Square test. The results of this study are that there is a significant relationship between family resilience and early marriage attitudes with a value (p-value 0.000) and reproductive health behaviour has a relationship with the attitude of early adolescent marriage with a value (p-value 0.006). The results of this study provide policy recommendations to the West Java Provincial Health Office in the form of adolescent reproductive health services in school settings.